السياسة الأمنية الأوروبية تجاه اللاجئين 2010-2016 - عبد الهادي, عباد (My University, 2016)
شهدت أوروبا موجة من اللاجئين لم يسبق لها مثيل, وكان لهذه الأحداث الأثر البالغ في تغير كثير من السياسيات الأوروبية على مختلف الأصعدة وخاصة الأمنية منها. فالنزاعات الداخلية في كل من سوريا والعراق وما خلفته تلك الوقائع على الاستقرار السياسي والأمني والاجتماعي والاقتصادي على المنطقة، زادت في تفاقم أزمة اللاجئين. مع الحالة الاقتصادية والأمنية لدول افريقيا جنوب الصحراء التي ادت الى نزوح الالاف من اللاجئين وانتقالهم نحو الدول الأوروبية خاصة دول الطوق والعبور كإيطاليا واليونان طالبين الحماية والأمان مواجهين ما يعترض طريقهم من مخاطر وصعوبات و مشاق كبيرة تهدد حياتهم. قصد الحصول على العيش اللائق لهم. وهذا ما جعل أوروبا الوجهة الاولى المفضلة للاجئين لتستقبل القارة أعدادا كبيرة، على الرغم من الاجراءات الشديدة التي تتقيد بها في مسائل اللجوء والهجرة. وهو ما أثر على السياسة الأوروبية الأمنية تجاه اللجوء وحملها أعباء وضغوطا لأجل السيطرة على الأزمة وتجاوزها بما يخدم المصالح الأوروبية. توصَّلت الدراسة إلى مجموعة من الاستنتاجات فيما يخص معالجة السياسة الأمنية الأوروبية تجاه أزمة اللاجئين ومن أبرزها أن السياسية الأمنية الأوروبية تجاه اللاجئين كانت سياسة منقسمة وغير موحدة، بين مجموعتين من الدول الأوروبية، المجموعة الأولى تعد ضمن خط الطوق والمواجهة الاولى لاستقبال اللاجئين وتتحمل العبء الأكبر في التعامل مع اللاجئين. وهذه المجموعة تطالب الدول الأوروبية الأخرى بالمساعدة في تحمل الأعباء وتوزيع العادل للاجئين على كافة الدول الأوروبية. بينما تعتبر بقية الدول الأوروبية الأخرى أن قضية اللاجئين هي مسألة تخص السياسة الداخلية Europe has witnessed a wave of unprecedented refugees, and these events have had a profound impact on the change in many European policies on various levels, especially security. Internal conflicts in both Syria and Iraq and the consequent political, security, social and economic stability of the region have exacerbated the refugee crisis. With the economic and security situation of the countries of sub-Saharan Africa, which led to the displacement of thousands of refugees and their transfer to European countries, especially the countries of the ring and transit, such as Italy and Greece, seeking protection and safety, facing the obstacles and difficulties and hardships that threaten their lives. In order to have a decent living for them. This has made Europe the preferred destination for refugees to receive large numbers of the continent, despite strict measures in the asylum and immigration issues. Which has affected the European security policy towards asylum and carry burdens and pressure for control and overcome the crisis in the interests of Europe. The study reached a number of conclusions regarding the treatment of the European security policy towards the refugee crisis. The most prominent of these is that the European security policy towards the refugees was a policy of division and non-uniform between two groups of European countries. The first group is within the ring line and the first confrontation to receive the refugees. With refugees. This group calls on other European countries to help shoulder the burdens and fair distribution of refugees to all European countries. While the rest of the other European countries that the issue of refugees is a matter of the internal policy of any state, and the process of reception of refugees are in accordance with the European plans prepared for it.
م.س .ح.ر
Keywords: Security Policy - Refugees - Common European Foreign Policy; السياسة الأمنية - اللاجئين- السياسة الخارجية الأوروبية المشتركة